Illusion in Architecture: An Alternative for Creating Virtual Environment to Support Efficient Site Utilization - Pradika, Ferian Yavis; Samodra, FX Teddy Badai; Cahyadini, Sarah (Universitas Negeri Yogyakarta, 2024)
Virtual materiality has become a reality due to technological advancements. This affects the evolution of architecture. Land utilization in residential designs is currently unrestricted. Humans still exploit natural land and food supplies to build homes. Conversely, houses that merely use the land for viewing rather than traversing it are an example of inefficient land usage. In architecture, virtual materiality plays a part in creating an artificial world. In order to minimize land consumption, an architectural strategy that may introduce virtual materiality into the real world is required. Illusion is one tactic. Tricks and deceit are given priority in the illusion technique. This program is intended for home users who want to replace their natural surroundings with an artificial one. By using this method, nature can improve without requiring interference from the original environment. Modeling experiments and qualitative research are used in the research methodology. Create suggested concepts by using an architectural methodology. Rendering models and sketches are the research outputs. The findings demonstrate that home design can make use of illusion as a representation of virtual materiality. Through the application of matter illusion techniques, manufactured environments can be made to resemble natural ones. Implementing the material illusion in a trapezoidal home. Screen technology is used to do this. The center of the design is where screen technology is used to display environmental content. big horizontal and vertical sides are necessary. However, this can be a substitute for the natural environment for residents, especially in dwelling design.